Environmental regulations and technology : autothermal thermophilic aerobic digestion of municipal wastewater sludge - United States. Environmental Protection Agency. Center for Environmental Research Information; United States. Environmental Protection Agency. Risk Reduction Engineering Laboratory (Cincinnati, Ohio : United States Environmental Protection Agency, 1990)
55